1999
DOI: 10.1021/jf981091a
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Bioavailability of Natural Palm Oil Carotenoids and Synthetic β-Carotene in Humans

Abstract: Palm oil carotenoids are a mixture of alpha- and beta-carotenes, which are used as food colorants. They may also be applied as a functional food ingredient because of the provitamin A activity of alpha- and beta-carotenes and their proposed beneficial roles in the prevention of chronic diseases. This paper discusses the results of an incomplete balanced crossover study with 69 healthy adult volunteers to compare palm oil carotenoids with synthetic beta-carotene in their efficacies to increase plasma levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…This is the first study to compare a range of carotene and xanthophyll carotenoids using the Caco-2 in vitro model. Our results correlate with in vivo data (Kostic et al 1995; Gartner et al 1996; van Hof et al 1999) that have also shown higher percentage absorption of xanthophyll carotenoids compared to carotenes thus providing validation of this model as an approach to assess carotenoid availability. Additionally, our findings indicate that lower amounts of carotenoids were absorbed and transferred more efficiently than higher amounts suggesting a saturation effect.…”
Section: Discussionsupporting
confidence: 88%
“…This is the first study to compare a range of carotene and xanthophyll carotenoids using the Caco-2 in vitro model. Our results correlate with in vivo data (Kostic et al 1995; Gartner et al 1996; van Hof et al 1999) that have also shown higher percentage absorption of xanthophyll carotenoids compared to carotenes thus providing validation of this model as an approach to assess carotenoid availability. Additionally, our findings indicate that lower amounts of carotenoids were absorbed and transferred more efficiently than higher amounts suggesting a saturation effect.…”
Section: Discussionsupporting
confidence: 88%
“…Changes in plasma concentration following supplementation with the three carotenoids were clearly different, but in the absence of pharmacokinetictype studies it is not possible to conclude why. The amount of dietary fat present in a meal is known to affect the bioavailability and absorption of carotenoids (Jayarajan et al 1980;het Hof et al 1999;Stahl et al 2002), but even in the event of equal absorption, the carotenoids need not raise plasma concentrations to the same extent. Plasma concentrations reflect the degree and rate of absorption, patterns of tissue targeting and tissue loading.…”
Section: Discussionmentioning
confidence: 99%
“…β-carotene supplements in oil and natural food sources such as red palm oil have the highest bioavailability. 115 Bioavailability of carotenoids in plant matrices is a much more complex issue. Carotenoids in green leafy vegetables are located in chloroplasts and are bound to pigment-protein complexes that result in low bioavailability.…”
Section: Bioavailability Factorsmentioning
confidence: 99%